Limited usefulness of the IS6110 touchdown-PCR in blood for tuberculin skin test false-negative cattle with serological response to Mycobacterium bovis - Encinas, Micaela; Ferrara Muñiz, Ximena; Sammarruco, Romina Ayelén; Ruiz Menna, Victoria; Garro, Carlos Javier; Delgado, Fernando; Macías, Analía; Magnano, Gabriel; Zumárraga, Martín José; Garbaccio, Sergio Gabriel; Eirin, María Emilia (Frontiers in Veterinary Science, 2024)
Ante-mortem diagnosis of bovine tuberculosis (bTB) is based mainly on the tuberculin skin test (TST) and the ɣ-IFN release assay (IGRA). Some infected animals escape screening tests, thus, limit herd sanitation. Previous reports have suggested a predominant pattern of multi-organ lesions attributable to Mycobacterium bovis (the causative agent of bTB) bacteraemia. A case-control study was conducted to investigate blood PCR as an alternative tool for improving ante-mortem detection of TST false-negative bovines. Cases comprised 70 TST false-negative bovines (cases), which were serology positive, and controls included 81 TST positive bovines; all of them confirmed as infected with M. bovis. Detection of the IS6110 target through touchdown blood-PCR (IS6110 TD-PCR) was performed. The positivity of the blood-PCR was 27.2% in the control group. This performance was similar to the 15% obtained among cases (p=0.134). Most cases identified by the IS6110 TD-PCR exhibited focalized lesions (p=0.002). Results demonstrated that blood-PCR could detect TST falsenegative cattle, even if they are negative for IGRA. Considering that cases exhibited humoral response to M. bovis, further studies conducted in a pre-serological stage could provide evidence about the real contribution of the technique in herds.